2003
DOI: 10.1590/s0100-879x2003000700010
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide of the median preoptic nucleus (MnPO) in the alterations of salivary flow, arterial pressure and heart rate induced by injection of pilocarpine into the MnPO and intraperitoneally

Abstract: We investigated the effect of L-NAME, a nitric oxide (NO) inhibitor and sodium nitroprusside (SNP), an NO-donating agent, on pilocarpine-induced alterations in salivary flow, mean arterial blood pressure (MAP) and heart rate (HR) in rats. Male Holtzman rats (250-300 g) were implanted with a stainless steel cannula directly into the median preoptic nucleus (MnPO). Pilocarpine (10, 20, 40, 80, 160 µg) injected into the MnPO induced an increase in salivary secretion (P<0.01). Pilocarpine (1, 2, 4, 8, 16 mg/kg) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Note that, the hippocampal formation and adjacent areas were dramatically hypoperfused, as demonstrated by lack of visible, FITC‐albumin filled vessels. Taken together, these results suggest that pilocarpine caused two different cerebrovascular changes, one consisting of increased BBB permeability and the other related to hemodynamic changes (Saad et al, 2003).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Note that, the hippocampal formation and adjacent areas were dramatically hypoperfused, as demonstrated by lack of visible, FITC‐albumin filled vessels. Taken together, these results suggest that pilocarpine caused two different cerebrovascular changes, one consisting of increased BBB permeability and the other related to hemodynamic changes (Saad et al, 2003).…”
Section: Resultsmentioning
confidence: 81%
“…Non‐CNS effects of pilocarpine are observed at dosages much lower (1/20th) than those used to induce SE (Cook and Persinger, 1999). Very low dosages of peripherally administered pilocarpine (4 mg/kg) caused a substantial decrease in arterial pressure (Saad et al, 2003). Pilocarpine can also directly activate WBC, therefore decreasing the CD4/CD8 T‐lymphocyte ratio (Arzt et al, 1989; Prync et al, 1992).…”
mentioning
confidence: 99%
“…In brain slices or isolated guinea pig brain, seizure‐like events could be evoked by pilocarpine only in the co‐presence of elevated K + concentrations, mimicking actions that occur when BBB permeability function is compromised (3,4). Based on the premises established from previous work and showing that pilocarpine can directly activate muscarinic receptors on brain microvasculature and white blood cells (5,6), Marchi and colleagues reported the following three interesting findings:…”
Section: Commentarymentioning
confidence: 97%
“…It has been demonstrated that NO may facilitate the release of excitatory transmitters, possibly through a presynaptic cyclic GMP-dependent mechanism (Wu et al, 1997). The influences of NO of the central nervous system (CNS) on several physiological parameters such as salivary secretion have been demonstrated (Saad et al, 2002a(Saad et al, , 2003. Also these effects implicated the participation of septal area (Saad et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%